1973
DOI: 10.1128/jb.116.2.915-924.1973
|View full text |Cite
|
Sign up to set email alerts
|

Production and Characterization of the Slime Polysaccharide of Pseudomonas aeruginosa

Abstract: The slime polysaccharides produced by Pseudomonas aeruginosa isolated from a variety of human infections were investigated. Slime production in culture seemed optimal when adequate amounts of carbohydrate were present and under conditions of either high osmotic pressure or inadequate protein supply. The polysaccharides produced by the organisms were similar to each other, to the slime of Azotobacter vinelandii, and to seaweed alginic acids. They were composed of p3-1, 4-linked D-mannuronic acid residues and va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
182
2
3

Year Published

1992
1992
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 403 publications
(192 citation statements)
references
References 29 publications
(19 reference statements)
5
182
2
3
Order By: Relevance
“…A salient feature of the P. aeruginosa EPS is its heterogeneity based upon the clinical origin of the strains. The results of the present study sup-port and extend previous studies which show that Pseudomonas EPS is structurally similar to alginate produced by several species of marine algae [3], except that seaweed alginate was not acetylated. In addition, our data demonstrate that the extracellular material produced by strains of P. aeruginosa from patients with or without CF was composed mainly of alginate, except in the nonmucoid isolate from the bronchiectasic patient.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…A salient feature of the P. aeruginosa EPS is its heterogeneity based upon the clinical origin of the strains. The results of the present study sup-port and extend previous studies which show that Pseudomonas EPS is structurally similar to alginate produced by several species of marine algae [3], except that seaweed alginate was not acetylated. In addition, our data demonstrate that the extracellular material produced by strains of P. aeruginosa from patients with or without CF was composed mainly of alginate, except in the nonmucoid isolate from the bronchiectasic patient.…”
Section: Discussionsupporting
confidence: 88%
“…Other experiments also showed the heterogeneity of the alginates produced by mucoid P. aeruginosa from patients with or without CF [3,7,8,12]. Comparison of our data with these studies is not easy because of differences in the bacterial growth, variability in the EPS extraction and the chemical analyses; however, authors using identical analytical methods have found a similar composition of the alginate produced by mucoid isolates of P. aeruginosa from patients with or without CF [9,23].…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The EPS was purified according to Evans and Linker (1973). The purified EPS was then sent for carbohydrate analysis to the Complex Carbohydrate Research Center of the University of Georgia (USA).…”
Section: Analysis Of Bacterial Epsmentioning
confidence: 99%
“…In chronic CF airways, P. aeruginosa strains that have acquired selected phenotypes are recovered and such phenotypic changes are induced for survival in the harsh environment of the human lung (Burns et al, 2001;Hogardt et al, 2007;Mena et al, 2008). One of these changes is an overproduction of a capsule-like polysaccharide called alginate (Evans & Linker, 1973). Mucoid P. aeruginosa strains isolated from sputum of CF patients have a mutation in the mucA gene, encoding MucA, a negative regulator of AlgT that activates transcription of the alginate biosynthesis operon (Martin et al, 1993).…”
Section: Introductionmentioning
confidence: 99%